Penggunaan Bahasa dalam Komunikasi Tasya Farasya untuk Branding Produk "Mother Of Pearl" di Instagram - Zein Sheilawati Putri; Naida Nasywa Cahyarani; Muhammad Fadhlan Fauqa; Linggar Apritataqwa Giandivari; Natalia Desy Anggraeni (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2024)
Instagram has helped Tasya Farasya build her beauty brand called "Mother of Pearl". Tasya has created an emotional connection with her followers by using persuasive and engaging language, reflecting the brand's original, gentle, and luxurious values. Tasya has improved its brand image and increased its appeal in the Indonesian beauty market through innovative and interactive content. The strategic communication method she uses to increase the allure of "Mother of Pearl" products by displaying premium and elegant quality, in addition to expanding a loyal and engaged customer base.